Dinamika Kepercayaan Publik di Media Sosial: Krisis Komunikasi Humas Terhadap Isu Korupsi Pertamina - Faisal, Daffa; Berliana, Farida; Pahlevi, Reza; Febrian, Revi; Fathullah, Dzulham; al- Gozi, Ahmed; Ramadhani, Susan (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The communication crisis in the alleged corruption case of Pertamina shows how social media acts as the main arena in forming public opinion while testing the effectiveness of the company’s public relations communication strategy. Using a qualitative approach with virtual ethnographic methods, this study found that the dominance of negative sentiment towards Pertamina reflects the failure of public relations in managing public perception transparently and accountably. The company’s inability to provide fast and credible clarification open space for speculation and disinformation, worsening the existing trust crisis. Based on Situational Crisis Communication Theory (SCCT), defensive communication responses actually increase public skepticism, while agenda-setting theory shows that failure to control narration allows social media to take over discourse that is increasingly difficult to control. This finding confirms that in the digital era, crisis communication strategies must be more adaptive, proactive, and based on public involvement in order to avoid escalation of negative opinions that can damage the company’s reputation and related institutions.